A Case of Malignant Pheochromocytoma Detected during Fertility Treatment. (5th February 2014) - Hagiwara, Kazuhisa; Hamano, Itsuto; Kusaka, Ayumu; Murasawa, Hiromi; Tokui, Noriko; Imanishi, Kengo; Okamoto, Akiko; Yamamoto, Hayato; Imai, Atsushi; Hatakeyama, Shingo; Yoneyama, Takahiro; Hashimoto, Yasuhiro; et al.
Abstract : We report a case of malignant pheochromocytoma in a 35-year-old Japanese woman during fertility treatment, successfully treated with surgical excision. The patient recovered without any postoperative problems, and plasma catecholamine levels normalized. At present, 18 months after the operation, there are no signs of relapse.